Neuroanatomical Phenotypes Are Consistent With Autism‐Like Behavioral Phenotypes in the 15q11‐13 Duplication Mouse Model. Issue 5 (7th March 2015) - Ellegood, Jacob; Nakai, Nobuhiro; Nakatani, Jin; Henkelman, Mark; Takumi, Toru; Lerch, Jason
<x xml:space="preserve">Abstract</x> Paternally and maternally inherited deletions and duplications of human chromosome 15q11‐13 are relatively common in the human population. Furthermore, duplications in the 15q region are often associated with autism. Both maternal and paternal interstitial 15q11‐13 duplication mouse models have been previously created, where several behavioral differences were found in the paternal duplication (patDp/+) mouse but not in the maternal duplication (matDp/+). These included decreased sociability, behavioral inflexibility, abnormal ultrasonic vocalizations, decreased spontaneous activity, and increased anxiety. Similarly, in the current study, we found several anatomical differences in the patDp/+ mice that were not seen in the matDp/+ mice. Regional differences that are evident only in the paternal duplication are a smaller dentate gyrus and smaller medial striatum. These differences may be responsible for the behavioral inflexibility. Furthermore, a smaller dorsal raphe nucleus could be responsible for the reported serotonin defects. This study highlights consistency that can be found between behavioral and anatomical phenotyping. Autism Res2015, 8: 545–555. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.